Inuit Women’s Knowledge of Bird Skins and its Application in Clothing Construction, Sanikiluaq, Nunavut - Nakashima, Douglas (Material Culture Review, 2002)
This article is based upon a project carried out with the Qikirtamiut, Inuit of the Belcher Islands (Sanikiluaq, Nunavut), to reconstruct a woman’s child-carrying coat (amaqusik/ made from the skins of the Common Eider (Somateria mollissimaj. The Qikirtamiut, and in particular Qikirtamiut women, have developed an extensive corpus of knowledge about the skins of birds. This knowledge has its origins in their long history of use of bird skins for clothing. Their appraisal of the properties of these skins takes into account a variety of factors: species, age, sex, season of harvest, and condition. Qikirtamiut also differentiate between the properties of the feathered skin originating from different parts of the bird’s body. These factors confer upon bird skins specific properties that influence in their turn their use in clothing construction. This analysis reveals not only the extensive knowledge that Qikirtamiut women have developed about bird skins, but also furthers our understanding of the contrasting qualities desired for different parts of a single garment, the eider skin coat. Résumé Cet article se fonde sur un projet mené avec les Qikirtamiut, Inuits des Iles Belcher (Sanikiluaq, Nunavut), qui a permis la reconstruction d’un amaqusik, manteau de femme avec une poche pour bébé, fait de peaux d’eiders à duvet (Somateria mollissimaj. Les Qikirtamiut, en particulier les femmes, ont développé un corpus de savoir très étendu sur les peaux d’oiseaux, dont l’origine est ancrée dans une longue tradition d’utilisation de ces peaux pour le vêtement. Les Qikirtamiut évaluent les propriétés des peaux en fonction de nombreux facteurs : espèce, âge, sexe, saison de la récolte, condition physique et différentes parties du corps de l’animal. Les propriétés de ces peaux déterminent leur usage. En plus de révéler l’étendue du savoir que les femmes qikirtamiut ont développé, cette analyse permet de mieux comprendre les différentes qualités recherchées pour chaque partie d’un vêtement, le manteau en peau d’eider.